Potentiometric Studies on Nickel(II), Copper(II) and Zinc(II) Metal Complexes with New Schiff Bases Containing Cyclobutane and Thiazole Groups in 60% Dioxane-Water Mixture - Altun, Yueksel; Koeseoglu, Fitnat; Demirelli, Havva; Yilmaz, Ibrahim; Cukurovali, Alaattin; Kavak, Nusret (Soc Brasileira Quimica, 2009)
The acid-base equilibria of Schiff bases containing cyclobutane and thiazole functional groups and their copper(II), nickel(II) and zinc(II) complexes were investigated potentiometrically in 60% dioxane-water media at 25.0 +/- 0.1 degrees C and I = 0.10 mol L-1 NaClO4. The values of the protonation constants determined in this study, logK(OH), logK(NH(1)) and logK(NH(2)), are related to the protonation of the phenolate oxygen atom, the nitrogen atom on the thiazole ring and the imine nitrogen atom, respectively. The variation of the protonation constants of the Schiff bases was interpreted on the basis of structural factors. The Schiff bases form stable complexes with copper(II), nickel(II) and zinc(II) metal ions. There was not a meaningful correlation between the basicity of the Schiff bases and the stability constants of their complexes. Complex stabilities follow the trend copper(II) > nickel(II) > zinc(II), which is in agreement with the Irving-Williams series.
Keywords: cyclobutane; thiazole; protonation constants; stability constants